Molecular recognition of isomeric protonated amino acid esters monitored by ESI-mass spectrometry - Liesenfeld, Andrea; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2014)
Two new 9,9’-spirobifluorene-derived crown ethers were prepared and used to recognise constitutionally isomeric amino acid derivatives. The performance of the receptors was evaluated by ESI-mass spectrometry using the isomer labelled guest method (ILGM). This method revealed the preferred binding of L-norleucine and L-leucine compared to L-isoleucine for both receptors. Furthermore, non-covalent isotope effects demonstrate the relevance of dispersive interactions for the overall binding event. These effects also provide hints for the relative spatial orientation of the guest molecules within the host–guest complex, and thereby prove the importance of the spirobifluorene moiety for the observed binding of the protonated amino acid esters.
Keywords: amino acids; isomer labelled guest method (ILGM); mass spectrometry; molecular recognition; 9,9’-spirobifluorenes; template

(untitled) - Stein, W. H.; Moore, S.; Stamm, G.; Chou, C.-Y.; Bergmann, M. (J. Biol. Chem., 1942)

(untitled) - Hongo, C.; Yoshioka, R.; Yamada, S.; Chibata, I. (J. Chem. Technol. Biotechnol., 1979)

(untitled) - Martens, J.; Weigel, H. (Liebigs Ann. Chem., 1983)

(untitled) - Stoddard, M. P.; Dunn, M. S. (J. Biol. Chem., 1942)

(untitled) - McBride, R. W.; Jolly, D. W.; Kadis, B. M.; Nelson, T. E., Jr (J. Chromatogr., A, 1979)

(untitled) - Collins, B. E.; Wright, A. T.; Anslyn, E. V. (Top. Curr. Chem., 2007)

(untitled) - Kraus, T. (Curr. Org. Chem., 2011)

(untitled) - Mutihac, L.; Lee, J. H.; Kim, J. S.; Vicens, J. (Chem. Soc. Rev., 2011)

(untitled) - Joseph, R.; Rao, C. P. (Chem. Rev., 2011)

(untitled) - Urbach, A. R.; Ramalingam, V. (Isr. J. Chem., 2011)

(untitled) - Schneider, H.-J.; Agrawal, P.; Yatsimirski, A. K. (Chem. Soc. Rev., 2013)

(untitled) - Das, G.; Hamilton, A. D. (Tetrahedron Lett., 1997)

(untitled) - Cuntze, J.; Diederich, F. (Helv. Chim. Acta, 1997)

(untitled) - Li, C.-W.; Wang, C.-I.; Liao, H.-Y.; Chaudhuri, R.; Liu, R.-S. (J. Org. Chem., 2007)

(untitled) - Varela, J. A.; Peña, D.; Goldfuss, B.; Denisenko, D.; Kulhanek, J.; Polborn, K.; Knochel, P. (Chem.–Eur. J., 2004)

(untitled) - Tour, J. M.; Wu, R.; Schumm, J. S. (J. Am. Chem. Soc., 1990)

(untitled) - Czech, B.; Son, B.; Bartsch, R. A. (Tetrahedron Lett., 1983)

(untitled) - Dishong, D. M.; Diamond, C. J.; Cinoman, M. I.; Gokel, G. W. (J. Am. Chem. Soc., 1983)

(untitled) - Schalley, C. A. (Mass Spectrom. Rev., 2001)

Mass Spectrometry and Gas Phase Chemistry of Non-Covalent Complexes - Schalley, C. A.; Springer, A. (Wiley, 2009)

Chiral Recognition in the Gas Phase - Zehnacker, A. (CRC Press, Taylor & Francis Group, 2010)

(untitled) - Sawada, M. (Mass Spectrom. Rev., 1997)

(untitled) - Wade, D. (Chem.-Biol. Interact., 1999)

(untitled) - Kuchitsu, K.; Bartell, L. S. (J. Chem. Phys., 1962)

(untitled) - Pulay, P.; Meyer, W.; Boggs, J. E. (J. Chem. Phys., 1978)

(untitled) - Lacks, D. J. (J. Chem. Phys., 1995)

(untitled) - Felder, T.; Schalley, C. A. (Angew. Chem., 2003)
Angew. Chem., Int. Ed. 2003, 42, 2258–2260. doi:10.1002/anie.200350903

(untitled) - Rechavi, D.; Scarso, A.; Rebek, J., Jr (J. Am. Chem. Soc., 2004)

(untitled) - Liu, Y.; Warmuth, R. (Angew. Chem., 2005)
Angew. Chem., Int. Ed. 2005, 44, 7107–7110. doi:10.1002/anie.200501840

(untitled) - Mugridge, J. S.; Bergman, R. G.; Raymond, K. N. (J. Am. Chem. Soc., 2010)

(untitled) - Mugridge, J. S.; Bergman, R. G.; Raymond, K. N. (Angew. Chem., 2010)
Angew. Chem., Int. Ed. 2010, 49, 3635–3637. doi:10.1002/anie.200906569

(untitled) - Mugridge, J. S.; Bergman, R. G.; Raymond, K. N. (J. Am. Chem. Soc., 2012)

(untitled) - Matucha, M.; Jockisch, W.; Verner, P.; Anders, G. (J. Chromatogr., 1991)

(untitled) - Turowski, M.; Yamakawa, N.; Meller, J.; Kimata, K.; Ikegami, T.; Hosoya, K.; Tanaka, N.; Thornton, E. R. (J. Am. Chem. Soc., 2003)

(untitled) - Schmarr, H.-G.; Slabizki, P.; Müntnich, S.; Metzger, C.; Garcia-Moreno, E. (J. Chromatogr., A, 2012)